Três modos de ser revista: jornalismo e cotidiano em O cruzeiro, Realidade e Piauí - Nicoli Gloria de Tassis Guedes (2014)
This thesis investigates the different journalistic statutes performed by three important Brazilian magazines: Cruzeiro (1928-1970), Realidade (1966-1976) and piauí (2006 to present). Intending journalism as narrative and one of the spaces for circulation of discourses and the expansion / silenced of social voices, we are interested in investigating the transformation of everyday situations into events endowed with legitimacy. On the horizon, we signalize magazine journalism as a multiple and complex phenomenon. Therefore, we intend to foment understanding about the journalistic phenomenon, the construction of authority places in the Brazilian press and the relations between journalism, society and history, taking into account the symbolic disputes inside real narratives.